Intergenerational Cultural Conflicts and Discrimination Against Immigrants in Blinded by the Light Film - Maria Febrianti; Yosep B. Margono Slamet (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2025)
This paper examines the life struggles of Javed Khan, a second-generation Pakistani immigrant in the United Kingdom in Blinded by Light film. Culturally, as a Pakistani-British, Javed lives in two worlds, i.e., the old world belonging to his parents and his current world, the world he is living in, i.e., the British society and culture. To analyze this topic, the textual content analysis is employed. As for the theoretical framework, Hall’s concept of identity and some works of literature on discrimination are of importance. The result of the analysis shows that Javed’s journey reveals the challenges and pressures of adaptation and acculturation faced by second-generation immigrants in general, illustrating how the tension between intergenerational expectations often creates tension and fosters growth and understanding in a multicultural context. Javed is torn between the values of the home country his father holds and the values of the new country. In addition, the discrimination experienced by Malik Khan’s family reflects the experience of immigrant families in a broader context. The film encourages viewers to reflect on the societal expectations of immigrants to conform to the host society and culture, while also showcasing the importance of individual aspirations and self-expression.